Biological affinities among Western Siberian forest-steppe groups in the Early Iron age based on dental non-metric data (Bulletin of the International Association for Paleodontology, 2023)
The results of the study of the dental anthropology complexes of the population of the Sargat, Gorokhovo and Kashino cultures of the Early Iron Age in Western Siberia are presented. The study is based on the evaluation and statistical analysis of the frequencies of certain non-metric dental traits within each population. The source base of the study is 480 individuals from burials located in the Tobol, Ishim, Irtysh River regions, as well as on the territory of the Baraba forest-steppe zone. The aim of this study is to reconstruct the possible biological affinities between the Sargat, Gorokhovo and Kashino Cultures groups and Early Iron Age and Bronze Age tribes of Southern Urals and Western Siberia based of new dental non-metric data.The Sargat groups from the Tobol, Ishim and Irtysh regions and the Gorokhovo population reveal a weak biological affinity with the chronologically preceding population of Western Siberia of the Bronze Age. For the groups of these territories, the main component was introduced by the descendants of the carriers of the Petrovsky, Srubno-Alakul and Sintashta Cultures of the Southern Urals - the Savromats and Sarmatians. The affinities are especially strong among the Middle Sargat groups. Sargat population of Baraba demonstrated strong biological affinities to the local Late Bronze Age groups - the Fedorovo population and their descendants, Irmen Culture groups.Gorokhovo population reveals the same affinities as the Sargat groups. Relatedness between the Sargat and Gorokhovo groups and their contacts with the Sarmatians contributed to the convergence of their anthropological composition. Kashino Culture group is the most specific. Based on the results of study assumed divergence between Kashino and Sargat populations.